Gasto público en educación secundaria por alumno y el porcentaje de aprobados en la Región Loreto 2013-2019 - Flores Macedo, Cynthia (2024)
The objective of this research work is determined he relationship between public spending on high school per student and the percentage of passes in the Loreto region in the period 2013-2019, with the purpose of contributing with recommendations that reduce the unfavorable gap of Loreto with respect to the national average in percentage of approvals. The research was of a quantitative type, descriptive-correlational level and longitudinal non experimental design, which included as a study population all the statistical records on public spending, and students enrolled and approved in regular basic education institutions at the high school in the Loreto region. After applying the Pearson correlation coefficient, the existence of a positive relationship of 94.77% between public spending on high school per student and the percentage of passes in the Loreto region was verified.